Angular Ivy: Revolutionizing Rendering in Angular Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This paper examines the Angular introduced Ivy, a groundbreaking rendering engine that marked a significant milestone in the framework's evolution. Ivy enhances application performance and reduces bundle sizes by enabling more efficient tree-shaking and code generation. Its architecture facilitates faster compilation and improves debugging capabilities, offering clearer error messages and more straightforward code inspection. By introducing a new approach to handling templates and components, Ivy makes them more flexible and easier to understand. Additionally, it supports features like local and global components and improved dynamic component loading. This paper explores the innovations Ivy brings to Angular development, its impact on performance, and how it enhances the developer experience.